2007
DOI: 10.1021/ac062287+
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Pyridines into Fluorous Solvents Based on Hydrogen Bond Complex Formation with Carboxylic Acid Receptors

Abstract: A molecular receptor embedded in a 'poor-solvent' receiving phase, such as a fluorous phase, should offer the ideal medium for selective extraction and sensing. The limited solubility of most solutes in fluorous phases enhances selectivity by reducing the extraction of unwanted matrix components. Thus, receptor-doped fluorous phases may be ideal extraction media. Unfortunately, sufficient data do not exist to judge the capability of this approach. The solubilities of very few nonfluorous solutes are known. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…We have previously reported a detailed study on this complex. 12 The electronic absorption spectrum of isoquinoline in FC-72 ( Figure S10) has a πfπ* band at 262 and an nfπ* band at 315 nm that is rich in vibronic structure. A constant-volume titration of isoquinoline with 1 in FC-72 (Figures S10-S12) reveals two new nfπ* bands at 320 and 327 nm with addition of 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported a detailed study on this complex. 12 The electronic absorption spectrum of isoquinoline in FC-72 ( Figure S10) has a πfπ* band at 262 and an nfπ* band at 315 nm that is rich in vibronic structure. A constant-volume titration of isoquinoline with 1 in FC-72 (Figures S10-S12) reveals two new nfπ* bands at 320 and 327 nm with addition of 1.…”
Section: Resultsmentioning
confidence: 99%
“…These interactions become less important in competitive solvents; 10 thus, a matrix that is a poor solvent will provide a more selective environment for molecular recognition interactions. 11,12 Poorly solvating, highly nonpolar fluorous liquids are practically immiscible with both aqueous and organic phases 13 and, with the exception of some small gases, nonfluorous solutes are, in general, virtually insoluble in them. Thus, fluorous liquids have become useful for purification and reaction cleanup [13][14][15] by reducing the unintentional extraction of interfering species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been demonstrated that hydrogen bonds with the lone pair of nitrogen are more stable than the hydrogen bonds present in cyclic carboxylic acid dimers [85,86]. As a consequence, most nitrogen H-bond acceptors are more successful at competing for the carboxylic acid H-bonds than the carboxylic acids themselves [87]. This in turn results in the effective extraction of organic molecules comprising Lewis base characteristics as shown for pyridines [87,80].…”
Section: Phase Partitioning Into Fluorous Fluidsmentioning
confidence: 99%
“…Weber and coworkers studied the extraction of pyridines and porphyrin from an organic solvent to fluorous solvents using a carboxylic acid receptor. 29 Kondo and coworkers examined the extraction of organic acids into a hydrofluoroether using tri-n-butylphosphate (TBP) and a mixture of TBP and tri-n-octylamine (TOA). 30 The Buhlmann group's research on fluorous chemistry applied to ion-selective electrodes (ISEs) revealed that ionophore-doped fluorous membranes showed drastically enhanced selectivity, because of their extremely low polarity.…”
Section: Introductionmentioning
confidence: 99%